The use of the vulnerability factor in the study of vibration signals on the soil surface from the movement of subway electric trains - Senin, L.N.; Senina, T.Ye. (Geofizicheskiy Zhurnal, 2021)
Microseismic vibrations of the upper part of the soil strata occur continuously under the influence of endogenous and exogenous processes of both natural and artificial origin. Micro-oscillations of technogenic nature are especially characteristic of densely built-up urban areas. The practice of monitoring seismological monitoring observations shows that under such conditions it is possible to observe various types of microseismic vibrations, including elastic vibration signals in the frequency range of 1—100 Hz, generated by passing subway trains. In the calculations of the seismic stability of the designed structures, special attention is paid to the resonance characteristics of the upper part of the soil strata, which at certain frequencies can significantly enhance seismic vibrations, for example, from external vibrations sources. By traditional methods, the characteristics of resonant oscillations and their accounting are carried out, as a rule, with an insufficient degree of reliability and completeness, as a result of whichand so they are usually used as auxiliary ones. In this paper, a methodological complex is considered using modern methods for measuring and processing microseismic signals in order to identify areas with maximum amplitudes of response to external elastic influences in the study area for construction and take them into account in the future in design and construction. The study of vibroseismic noises formed on the surface of the soil layer, for example, by passing subway trains, allows one to estimate the amplitude-frequency properties of these soils, and the spectral ratio of horizontal displacements of soils to vertical H/V and the derivative of these ratios — the coefficient of vulnerability of the Ky — provide a confident selection of weakened zones that are subject to the greatest impact of external elastic vibrations.